CONTENT AND STRUCTURE OF THE AUTHOR’S DISCIPLINE “TECHNIQUES OF PEDAGOGICAL MANAGEMENT” - Marianna V. Shvardak (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология)
It was found that techniques today is the key to effective management of educational institutions in general and teachers in particular. It determines the search for those management tools that can be used effectively in the pedagogical process. The technicalization of pedagogical management contributes to its rationalization, eliminates those actions of the superior and specialists that are not necessary to achieve the expected result of management, formalizes the implementation of management functions. The article reveals the specifics of studying the author’s discipline «Techniques of pedagogical management», which is taught to applicants of the second (master’s) level of higher education specialty 011 «Educational, pedagogical sciences» (specialization «Management of educational institutions») at Mukachevo State University. This discipline is aimed at the holistic formation of the readiness of a future leader to apply the techniques of pedagogical management in a general secondary education institution. The scope of the discipline, subject, purpose, tasks, interdisciplinary connections are determined; the system of knowledge, skills, general and professional competencies. The system of professionally important competencies on which this discipline is focused is also defined: the ability to unite the teaching staff, to turn it into a team of like-minded people; to develop leadership, unconsciously evoke feelings of admiration and respect in teachers, students, their parents, etc.; monitoring the educational activities of general secondary education institutions; strategic planning of educational institution development; delegation of powers; making management decisions, willingness to take due responsibility for them; establishing a favorable positive atmosphere in the team; effective communication with participants in the educational process of general secondary education; rational use of working time; management of the institution by means of cloud technologies; effective use of marketing communication tools, etc. The expected training results of future managers are determined. The structure of the discipline is given: content modules, and topics. The main methods of training and control of applicants’ knowledge are also identified. The specifics of studying the theoretical and practical material of the discipline are outlined.